Internal Spreading of Papillary Thyroid Carcinoma: A Case Report and Systemic Review - Hui Jin; Huanhuan Yan; Huamei Tang; Miao Zheng; Chaojie Wu; Jun Liu (Case Reports in Endocrinology)
An 18-year-old female diagnosed finally as PTC with intrathyroid spread was reported, and the diagnosis and surgical treatment of internal spreading of PTC were discussed. One lump was found on the thyroid isthmus by physical examination and B ultrasound, and multiple nodular shadows were found by CT. This patient finally underwent total thyroidectomy with bilateral central node dissection due to multifocal papillary thyroid carcinoma except PTC in the isthmus found in right lobe by intraoperative frozen section. The pathological section showed a major thyroid carcinoma in thyroid isthmus with scattered micropapillary carcinoma around it in the whole thyroid gland. The small lesions are distributed around central lesion in a radial form and the number of small lesions decreases with increased distance from central lesion. PTC with internal spread should be distinguished from multifocal PTC and poorly differentiated PTC in pathology. Thyroid cancerous node had a large diameter; it was likely to have internal spread. Combined imaging before surgery should be valued to diagnose PTC with internal spread. Preoperative CT and intraoperative frozen section are helpful for surgical volume selection of PTC with internal spread.